The design and implementation of advanced driver assistance system (ADAS) data acquisition engine based on heterogeneous computation platform - Jumaah, Fawaz Mohammed (Tanjong Malim, 2021)
The design and implementation of advanced driver assistance system (ADAS) data acquisition engine based on heterogeneous computation platform by Jumaah, Fawaz Mohammed